Effects from probiotics about the intestinal microbiota and metabolism in seniors (Research, Society and Development, 2020)
The elderly go through funcional, biological, psychological and mobility changes of the gastrointestinal system. These changes can favor the starting point of a variety of deseases related to the gastrointestinal system, including intestinal dysbiosis. As a resulto f these problems, the funcional foods are being widely used to modulate the intestinal microbiata, the imune system and to improve the intestinal funtions, mainly through the use of probiotics . The aim of the present study was to demonstrate the importance of using probiotics to improve intestinal dysbiosis in elderly patients and improve quality of life. It is an integrative review, using as descriptors: metabolism, seniors, probiotic, intestinal microbiota. The databases used were Science Direct, MEDLINE and Web of Science. Inclusion criteria were publications in English, Portuguese and Spanish from 2009 to 2019 and texts available in full. In all, 43 articles were found, of which 12 were used for study composition. As a result, it was observed that probiotics favor a number of beneficial health effects such as: preservation of intestinal integrity, decreased cholesterol levels, glycemic control, anticarcinogenic effect decreased proinflammatory cytokine production, improved immune system and reduced intestinal infections, it is a useful tool to prevent some disorders that affect the elderly, especially those related to the immune system. However, it is emphasized the need for further studies, due to its complexity and influence on various organs and metabolic pathways.